HUBUNGAN FUNGSIONAL PERTUNJUKAN TEATER BUAH TANGAN DARI UTARA DENGAN KONDISI WARGA CELUKAN BAWANG - Pasha Maraneka, I Putu Reza; Nugroho, Wahyu Budi; Kamajaya, I Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT The goals of this research is to explain and analyse any functional relations between â€˜â€™Buah Tangan dari Utaraâ€™â€™ performance,withal Celukan Bawangâ€™s. This community is having problem with PLTU. â€˜â€™Buah Tangan dari Utaraâ€™â€™ is a performance of â€œKalanganâ€ theathre, there are many scenes that explains about Celukan Bawangâ€™s and the developerâ€™s conflict. Gurvitchâ€™s sociology of the theatre thought is the theory base, he explained theatre performance can have goals for spesific social framework. Secondly, functional relations of the theater show to social reality. Thirdly, by social function approach in theathre performance. This reseacrh is using a descriptive research method with qualitative research type, any data collection method is applied to gained accurate data. By Gurvitch concept, functional relation of â€œBuah Tangan dari Utaraâ€ performance can be any representation of symbolic social reality of Celukan Bawang in the dimension of economic, social, environment and health againts PLTU construction Keywords: Celukan Bawang, Buah Tangan Dari Utara, sociology of the theater